Harnessing farmer-led adaptation for sustainable livestock systems - International Livestock Research Institute (International Livestock Research Institute, 2022)
Climate change is affecting food producers in developing countries. CGIAR is at the forefront of harnessing farmer-led adaptation for sustainable livestock systems to help transform global food systems